Breastfeeding Mothers' Consumption and Perceived Efficacy of Foods, Beverages, and Herbal Supplements to Increase Milk Supply. (7th June 2021) - Ryan, Rachel; Hepworth, Allison; Bihuniak, Jessica
Abstract: Objectives: Perceived insufficient milk is a common reason that mothers wean prior to the Academy of Pediatrics recommended 6 months of exclusive breastfeeding with continued breastfeeding through ≥ 12 months. Prior research indicates that mothers modify their dietary intake to address milk supply concerns. The current study fills a gap in the literature regarding the prevalence, perceived efficacy, and predictors of foods, beverages, and herbal supplements that U.S. mothers consume to increase milk supply. Methods: Paid Facebook advertisements were used to recruit breastfeeding mothers (≥18 years, living in the U.S.) into an online, cross-sectional survey. Participants self-reported their demographic characteristics, breastfeeding experiences, and consumption and perceived efficacy of 11 foods, 7 beverages, and 9 herbal supplements for increasing milk supply. Descriptive statistics were calculated for all study variables. The association between maternal perceived insufficient milk and consumption of any foods/beverages (yes/no) or any herbal supplements (yes/no) to increase milk supply was examined via Fisher's exact tests. Results: Participants (N = 192) primarily identified as white (90%) and married or partnered (94%); 15% were WIC participants. Most (84%) felt they produced enough milk to satisfy their child. Over half (55%) previously or currently consumed foods/beverages to increase milk supply, and 29% consumed herbal supplements. The most commonly consumed foods/beverages were oats (47%), sports drinks (34%), store-bought lactation cookies (26%) and lactation tea (20%). Store-bought lactation cookies were perceived as the most effective at increasing milk supply (50%). The most commonly consumed herbal supplement was a combination supplement (25%), of whom, 40% believed it increased milk supply. Fenugreek was the most commonly consumed single herbal supplement (13%); 42% believed it increased milk supply. Maternal perceived insufficient milk was associated with ever consuming foods/beverages to increase milk supply (p = .04), and herbal supplements (p = .02). Conclusions: Many breastfeeding mothers consume foods, beverages and/or herbal supplements to increase milk supply, signaling an urgent need for research on the effects of dietary intake on human milk production, and maternal and child health outcomes. Funding Sources: None.